Isolated colonic neurofibroma revealed by a painful abdominal mass - Fulgence, Kassi A. B.; K., Yenon; Justin, N’dah K.; M., Traore (International Surgery Journal, 2016)
The authors talk about one rare case of isolated colonic neurofibroma in a black woman of 37-years-old who had consulted for a painful abdominal mass, two month after an elective caesarean. The colic tumours are rare and particularly, the isolated neurofibromas of the colon are exceptional. We notice the diagnostics difficulties. We insist on the necessary of the anatomo-pathology exam of the surgical specimen and on the importance of the control for never return a malignant degeneration.